2014
DOI: 10.17265/2328-7136/2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Surveillance of Airborne Fungi Contaminating Intensive Care Units and Operation Rooms in Assiut University Hospitals, Egypt

Abstract: Mycoflora of atmospheric air and dust samples collected from air conditioning systems in 12 of each I.C.U. (intensive care units) and O.R. (operation rooms) were tested using settle and dilution plate methods on four types of agar media and incubated at 25 °C. Forty-five fungal species representing 23 genera were isolated and identified. The most prevalent genera recorded were Cladosporium, Aspergillus, Penicillium and Fusarium. The total colony forming units of airborne fungi recovered in I.C.U. and O.R. rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…These all are common genera frequently isolated from indoor environments of hospital and air conditioning systems. Even though these are apparently harmless for healthy people, it may be unsafe for the patients of risk groups (immuno-suppressive, immune-compromised, and immune-competent), especially those treated in surgical wards, newborn ward, and intensive care units [36][37] . Other species that had been isolated in our case study with low concentration reported having antagonistic health symptom 38 .…”
Section: Discussionmentioning
confidence: 99%
“…These all are common genera frequently isolated from indoor environments of hospital and air conditioning systems. Even though these are apparently harmless for healthy people, it may be unsafe for the patients of risk groups (immuno-suppressive, immune-compromised, and immune-competent), especially those treated in surgical wards, newborn ward, and intensive care units [36][37] . Other species that had been isolated in our case study with low concentration reported having antagonistic health symptom 38 .…”
Section: Discussionmentioning
confidence: 99%